Neocytolysis: none, one or many? A reappraisal and future perspectives - Risso, Angela; Ciana, Annarita; Achilli, Cesare; Antonutto, Guglielmo; Minetti, Giampaolo (Frontiers in Physiology, 2014)
Neocytolysis is the hypothesis formulated to explain experimental evidence of selective lysis of young red blood cells (RBCs) (neocytes) associated with decreased plasma levels of erythropoietin (EPO). In humans, it appears to take place whenever a fast RBC mass reduction is required, i.e. in astronauts during the first days of spaceflight under weightlessness, where a fast reduction in plasma volume and increase in haematocrit occur. EPO plasma levels then decline and a decrease in RBC mass takes place, apparently because of the selective lysis of the youngest, recently generated RBCs (neocytes). The same process seems to occur in people descending to sea level after acclimatization at high altitude. After descent, the polycythaemia developed at high altitude must be abrogated, and a rapid reduction in the number of circulating RBCs is obtained by a decrease in EPO synthesis and the lysis of what seem to be young RBCs. In vivo, neocytolysis seems to be abolished by EPO administration. More recent research has ascribed to neocytolysis the RBC destruction that occurs under such disparate pathophysiologic conditions as nephropathy, severe obstructive pulmonary disease, blood doping, and even malaria anaemia. According to the theory, EPO’s central role would be not only to stimulate the production of new RBCs in conditions of anaemia, as maintained by the orthodox view, but also that of a cytoprotective factor for circulating young RBCs. Why neocytes are specifically destroyed and how is this related to decreased EPO levels has not yet been elucidated. Changes in membrane molecules of young RBCs isolated from astronauts or mountain climbers upon return to normal conditions seem to indicate a higher susceptibility of neocytes to ingestion by macrophages. By limiting the context to space missions and high altitude expeditions, this review will address unresolved and critical issues that in our opinion have not been sufficiently highlighted in previous works.